Integrating Local Culture Into the English Language Teaching and Learning Process: Penelitian - Putra Darma, Virga; Maesaroh, Siti; Ria Citra, Alina (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This study aims to explore the integration of local cultures in the English language learning process at the high school level. In the context of globalization and the dominance of foreign cultures in English teaching materials, it is important to preserve local identity and enrich students' learning experiences through contextual and meaningful approaches. Using a qualitative approach, this study involved 42 respondents consisting of teachers and students from various regions in Cirebon. Data was collected through the Goggle Form open questionnaire. To understand the perception of experience, as well as teaching practices that involve elements of local culture. The results of this study show that the integration of local cultures can increase students' motivation to learn, strengthen their sense of cultural identity, and encourage the use of English in contexts relevant to their lives. Cultural elements such as folklore, traditional dances, special foods, local festivals are used creatively in teaching and learning activities. However, challenges also arise, such as a lack of resources, difficulties in designing culturally-based materials, and the need for in-depth teacher training. This study recommends the development of education policies that support the systematic inclusion of local culture in foreign language teaching, as well as strengthening the capacity of teachers in implementing culture-based approaches.